History of Higher Education in Canada - Sheehan, Nancy M. (Canadian Journal of Higher Education, 1985)
This paper relates the changes that have occurred in historiography over the last couple of decades to the present state of writing on the history of higher education in Canada. The existing bibliography has laid the groundwork and the 'new' history offers the means by which the complex relationships between society and institutions of higher learning can be synthesized. A few examples of the kinds of questions that need to be asked and of some assumptions that need analysis are given. By looking at all phases of universities - professors, students, women, administrative and academic matters; by using quantitative as well as qualitative research techniques; by consulting government, church, local and business sources as well as university material; and by analyzing and critiquing the newer historians of higher education can help Canadians understand the traditions and mores of individual institutions as well as the collective impact of higher education on the society.